Volver - Pedro Almodóvar (2006)
Raimunda lives in Madrid with her daughter Paula and her husband Paco who's always drunk. Her sister Sole is separated and work clandestinely as a hairstylist for women. The two sisters lost their parents in a fire in La Mancha their birth village years ago. In the village remains only their aunt Paula that continue to speak about her sister Irene, mother of the two, like if she is still alive. When the old aunt die the situation change and the past come back (Volver) again, in a twist of mystery and suspense.
Keywords: Comedy, Drama